Prediksi Settlement Pondasi Tiang Cara Hand Method vs Pile Driving Analysis (PDA) di Kota Palembang - Livian Teddy (Universitas Bandar Lampung (UBL), 2013)
Foundation reduction calculation end bearing foundation and friction pilehand Boussinesq theory method based on the simplification of the theory of soil mechanics. To determine the level of accuracy of the calculation of this hand method, conducted a comparison with the results of a decrease in the pole using a PDA Test . It is assumed that there is a positive correlation between the decrease in mast results of Static Load Test and PDA Test, so that PDA Test results of the settlement can be considered to replace the results of the settlement of Static Load Test.Comparison of reduction in foundation using hand method borepile Boussinesq theory and the PDA Test conducted at 3 locations in the city of Palembang. The result shows that the calculation of hand method Boussinesq theory can predict a moderate decrease in pile foundation in these three locations. In addition, a practical calculation for settlement of the pole, based on the ultimate load of the column, so the decline in each column can be estimated, so that differential settlement can be predicted. —Perhitungan penurunan pondasi end bearing dan friction pilehand method teori Boussinesq didasarkan penyederhanaan teori mekanika tanah. Untuk mengetahui tingkat keakurasian perhitungan hand method ini diperbandingkan dengan penurunan tiang hasil PDA Test. Dengan asumsi dengan adanya korelasi positif antara penurunan tiang hasil Static Load Test dan PDA Test, sehingga hasil settlement PDA Test dapat dianggap menggantikan hasil settlement dari Static Load Test. Perbandingan penurunan pondasiÂ borepile hand method teori Boussinesq dan PDA Test yang dilakukan 3 lokasi di Kota Palembang menunjukkan perhitunganÂ hand method teori Boussinesq secara moderat dapat memprediksi penurunan pondasi tiang di ketiga lokasi. Selain itu perhitungan praktis settlement tiang ini didasarkan pada beban ultimit kolom sehingga penurunan masing-masing kolom dapat diestimasi sehingga differential settlement dapat diprediksi.